Inactivation Effect of Violet and Blue Light on ESKAPE Pathogens and Closely Related Non-pathogenic Bacterial Species – A Promising Tool Against Antibiotic-Sensitive and Antibiotic-Resistant Microorganisms - Hoenes, Katharina; Bauer, Richard; Meurle, Tobias; Spellerberg, Barbara; Hessling, Martin (Frontiers in Microbiology, 2021)
Due to the globally observed increase in antibiotic resistance of bacterial pathogens and the simultaneous decline in new antibiotic developments, the need for alternative inactivation approaches is growing. This is especially true for the treatment of infections with the problematic ESKAPE pathogens, which include Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter species, and often exhibit multiple antibiotic resistances. Irradiation with visible light from the violet and blue spectral range is an inactivation approach that does not require any additional supplements. Multiple bacterial and fungal species were demonstrated to be sensitive to this disinfection technique. In the present study, pathogenic ESKAPE organisms and non-pathogenic relatives are irradiated with visible blue and violet light with wavelengths of 450 and 405 nm, respectively. The irradiation experiments are performed at 37°C to test a potential application for medical treatment. For all investigated microorganisms and both wavelengths, a decrease in colony forming units is observed with increasing irradiation dose, although there are differences between the examined bacterial species. A pronounced difference can be observed between Acinetobacter, which prove to be particularly light sensitive, and enterococci, which need higher irradiation doses for inactivation. Differences between pathogenic and non-pathogenic bacteria of one genus are comparatively small, with the tendency of non-pathogenic representatives being less susceptible. Visible light irradiation is therefore a promising approach to inactivate ESKAPE pathogens with future fields of application in prevention and therapy.